Visual Opsin Diversity in Sharks and Rays. (26th November 2019) - Hart, Nathan S; Lamb, Trevor D; Patel, Hardip R; Chuah, Aaron; Natoli, Riccardo C; Hudson, Nicholas J; Cutmore, Scott C; Davies, Wayne I L; Collin, Shaun P; Hunt, David M
Abstract: The diversity of color vision systems found in extant vertebrates suggests that different evolutionary selection pressures have driven specializations in photoreceptor complement and visual pigment spectral tuning appropriate for an animal's behavior, habitat, and life history. Aquatic vertebrates in particular show high variability in chromatic vision and have become important models for understanding the role of color vision in prey detection, predator avoidance, and social interactions. In this study, we examined the capacity for chromatic vision in elasmobranch fishes, a group that have received relatively little attention to date. We used microspectrophotometry to measure the spectral absorbance of the visual pigments in the outer segments of individual photoreceptors from several ray and shark species, and we sequenced the opsin mRNAs obtained from the retinas of the same species, as well as from additional elasmobranch species. We reveal the phylogenetically widespread occurrence of dichromatic color vision in rays based on two cone opsins, RH2 and LWS. We also confirm that all shark species studied to date appear to be cone monochromats but report that in different species the single cone opsin may be of either the LWS or the RH2 class. From this, we infer that cone monochromacy in sharks has evolved independently on multiple occasions. Together with earlier discoveries in secondarily aquatic marine mammals, this suggests that cone-based color vision may be of little use for large marine predators, such as sharks, pinnipeds, and cetaceans.